2019
DOI: 10.1021/acsbiomaterials.9b00362
|View full text |Cite
|
Sign up to set email alerts
|

Development of Zoledronic Acid-Based Nanoassemblies for Bone-Targeted Anticancer Therapy

Abstract: Bone metastasis occurs in the majority of cancer patients, which hampers quality of life and significantly decreases survival. Aggressive chemotherapy is a traditional treatment regimen that induces severe systemic toxicities. Therefore, bone-directed therapies are highly warranted. We report a novel nanoparticle formulation that is composed of poly­(vinylpyrrolidone) and tannic acid core nanoparticles (PVT NPs) that forms self-assembly with zoledronic acid (ZA@PVT NPs). The construction of ZA@PVT NPs was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Moreover, a targeted delivery strategy shows great potential to solve systemic toxic effects and multidrug resistance, which are longstanding problems with the standard cancer chemotherapy treatment. 142,143 Bone-modifying agents with a high affinity for bone are used for active bone targeting, including alendronate, [144][145][146] zoledronic acid, [147][148][149] aspartic acid, 150 denosumab, 151 and aptamers. 152,153 Nanomaterials and their drug delivery systems have unique advantages for the treatment of bone tumors.…”
Section: Systemic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a targeted delivery strategy shows great potential to solve systemic toxic effects and multidrug resistance, which are longstanding problems with the standard cancer chemotherapy treatment. 142,143 Bone-modifying agents with a high affinity for bone are used for active bone targeting, including alendronate, [144][145][146] zoledronic acid, [147][148][149] aspartic acid, 150 denosumab, 151 and aptamers. 152,153 Nanomaterials and their drug delivery systems have unique advantages for the treatment of bone tumors.…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…Bone-modifying agents with a high affinity for bone are used for active bone targeting, including alendronate, 144 146 zoledronic acid, 147 149 aspartic acid, 150 denosumab, 151 and aptamers. 152 , 153 Nanomaterials and their drug delivery systems have unique advantages for the treatment of bone tumors.…”
Section: A New Strategy For Tumor Therapy and Bone Regenerationmentioning
confidence: 99%
“…TA/polyvinylpyrilidone/zoledronic acid self-assembled nanoparticles particle size of ca. 400 nm, targeted mice bones and prostate tumor tissues in an exvivostudy as well as enhanced drug delivery to tumor cells [ 68 ].…”
Section: Combinational Approach Of Ta With Conventional Chemothermentioning
confidence: 99%
“…And targeted NPs provided all treated mice protection from bone lesions while 33% of the mice with nontargeted NPs treatment had bone lesions (Gdowski et al, 2017). Similarly, polymeric NPs or micelles encapsulating anticancer drugs, functionalized with ZA or ALN for homing bone, were designed in many other studies and demonstrated much higher efficiency and accumulation in bone than free drugs (Rudnick-Glick et al, 2016;Hatami et al, 2019;Liu, Romanova, et al, 2019). A novel preparation of polymeric NPs with high affinity to bone was completed by Yuya Hirano et al (Hirano & Iwasaki, 2017).…”
Section: Mono Target Deliverymentioning
confidence: 99%
“…In the affinity assay for HA in vitro , 77.5% of alendronate (ALN, Ald, or Alen) bound to HA powder (Ryu et al., 2016 ). Zol exhibited 20-fold increased targeting of bone metastatic lesions than other major tissues (Hatami et al., 2019 ). BP was used mostly to modify the designed NPs which encapsulated anticancer drugs.…”
Section: Drug Distribution Optimizationmentioning
confidence: 99%